Cerminan Masyarakat dalam Cerpen Malim Pesong Karya Hasan Al Bana: Kajian Sosiologi Sastra Ian Watt - Sihombing, M. Sholeh; Manurung, Jhosua M.; Panjaitan, Roy Pandapotan; Sinaga, Christian; Anggreini, Heny (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to see how the reflection of society is shown in the short story Malim Pesong by Hasan Al Bana. This study uses a qualitative descriptive research method. The data sources obtained in this study are story excerpts in the form of sentences, paragraphs, or dialogues from part of the contents of the short story Malim Pesong by Hasan Al Bana, based on the study of Ian Watt's sociology of literature. The data collection technique in this study uses reading techniques and note-taking techniques. This study is analyzed based on several contexts based on Ian Watt's views related to the study of sociology of literature, namely (a) the social context of the author, (b) the social reflection of community life, and (c) the social function of literature. This research resulted in findings in the form of the discovery of three literary sociological contexts belonging to Ian Watt in the short story Malim Pesong, which is a reflection of society in the literary work. The limitation of this study is the difficulty of understanding some sentences in the short story because some sentences are written in language that is difficult to digest.